Does spelling instruction make students better spellers, readers, and writers? A meta-analytic review - Graham, Steve; Santangelo, Tanya (Reading & writing, 2014)
Despite the importance of spelling for both writing and reading, there is considerable disagreement regarding how spelling skills are best acquired. During this and virtually all of the last century, some scholars have argued that spelling should not be directly or formally taught as such instruction is not effective or efficient. We conducted a comprehensive meta-analysis of experimental and quasi-experimental studies to address these claims. The corpus of 53 studies in this review included 6,037 students in kindergarten through 12th grade and yielded 58 effect sizes (ESs) that were used to answer eight research questions concerning the impact of formally teaching spelling on spelling, phonological awareness, reading, and writing performance. An average weighted ES was calculated for each question and the quality of included studies was systematically evaluated. Results provided strong and consistent support for teaching spelling, as it improved spelling performance when compared to no/unrelated instruction (ES = 0.54) or informal/incidental approaches to improving spelling performance (ES = 0.43). Increasing the amount of formal spelling instruction also proved beneficial (ES = 0.70). Gains in spelling were maintained over time (ES = 0.53) and generalized to spelling when writing (ES = 0.94). Improvements in phonological awareness (ES = 0.51) and reading skills (ES = 0.44) were also found. The positive outcomes associated with formal spelling instruction were generally consistent, regardless of students’ grade level or literacy skills.